PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII4 SMP NEGERI 17 PEKANBARU - Elvi, Mariyanti; Heleni, Susda; Kartini, Kartini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractThe research was classroom action research. This research aims to improve learning process and outcomes students by implementing cooperative learning type Two Stay Two Stray. The subject of the research is students of class VII4 of SMPN17 Pekanbaru in the first semester academic years 2012/2013. There are 40 students in the class, consisting 18 girls and 22 boys. The research are two cycles. Each cycle has four stages, the stages are planning, action, observation and reflection. The results showed the activity of teachers and students have done well after doing the action. An increase in the number of students who achieved at UH KKM end of each cycle compared to the number of students who achieve KKM on base score, increasing the number of students who scored 20 and 30 compared to the development of the number of students who received grades 5 and 10 as well as the increase in the average value of students from the first cycle to the second cycle. From the results of this study concluded that Cooperative Learning Type of Two Stay Two Stray can improve the students’ learning achievement at class VII4 of SMPN17 Pekanbaru in the first semester academic years 2013/2014.Key Word : Mathematics Learning Outcome, Cooperative Learning Type Two Stay Two Stray, Class Action Research.